New U-Th dates from Vindija, Velika pećina (Kličevica) and Mujina pećina and their implications for chronology of the Middle Paleolithic in Croatia : Novi rezultati datiranja Vindije, Velike pećine (Kličevica) i Mujine pećine U-Th metodom i njihova implikacija za kronologiju srednjeg paleolitika u Hrvatskoj - Karavanić, Ivor (Array, 2021)
This paper reports new results obtained by Uranium-Thorium (U-Th) dating of animal bones, tooth and flowstone samples from three Croatian Middle Paleolithic sites. Dates were obtained on bones and teeth from Vindija (Hrvatsko zagorje) and flowstones from Velika pećina in Kličevica and Mujina pećina (both in Dalmatia). Obtained results support the previously established chronology of the Middle Paleolithic of Croatia by confirming that the oldest layers of Vindija belong to MIS 6 and that Velika pećina in Kličevica was visited by Neandertals after 40 ka BP.